Experimental and analytical study on lightly reinforced concrete frames and beam-column joints - Tan, Haiyang (2008)
This project investigates the behaviour of lightly reinforced concrete beam-column joints and wide beam-column joints under simulated earthquake excitation-reversed cyclic loadings. The scope of this project includes experimental investigations on the seismic performances of beam-column joints, analytical investigation on either reinforced concrete frames or beam-column joints via a FEM approach, and the parametric study on the beam-column connections.